Symbiosis Relationship and Symbiosis Quality Evaluation of Regional Tourism: A Case Study on the Greater Changbai Mountains Tourist Area - Yixuan Wu (Hindawi Limited, 2021)
This paper aims to fully tap the value of the tourism brand of Changbai Mountains scenic area, give play to the radiation effect of the brand, and create the Greater Changbai Mountains (GCM) tourist area, thereby enhancing the coordinated development of regional tourism. Specifically, symbiosis correlation and symbiosis density were adopted to recognize the tourism symbiosis units in the core region of GCM tourist area, and an evaluation model was established for the tourism symbiosis quality in the core region of GCM tourist area. Based on the evaluation results, the places within the core region were divided into multiple levels. The results show that the core region of GCM tourist area covers Yanji City, Dunhua City, Hunchun City, Antu County, Baishan City, Fusong County, Changbai County, and Tonghua City, and these places fall on three different development levels.